The impact of potential Brexit scenarios on German car exports to the UK: An application of the gravity model - Jacqueline Karlsson; Helena Melin; Kevin Cullinane (Journal of Shipping and Trade (JST), 2018)
The objective is to forecast the impact of potential Brexit scenarios on the export volume of passenger cars from Germany to the UK. Based on Germany's total export volume of passenger cars, a double-logarithmic gravity model is specified and estimated using Ordinary Least Squares (OLS) regression. The final estimated model has strong explanatory power, with all variables significant at the 5% level. This is used for forecasting future export volumes under different Brexit scenarios. Diagnostic tests suggest that the model is robust and efficient. All tested Brexit scenarios are found to negatively impact passenger cars export volumes from Germany to the UK. The level of tariffs is found to have the most significant effect, but lower GDP due to Brexit is forecast to offset the benefits of trading with lower tariffs. The most pessimistic scenario for 2030 forecasts is a reduction of 15.4% compared to the "no Brexit" base-case scenario.
Keywords: 650; Automotive industry; Cars; Brexit; Gravity model; Trade Forecasts